Internet of Things based Smart Irrigation Control System for Paddy Field - Li-Wei Liu; Mohd Hasmadi Ismail; Yu-Min Wang; Wen-Shin Lin (AGRIVITA, Journal of Agricultural Science, 2021)
This study aimed to establish a water-saving irrigation technique-based Smart Field Cultivation Server (SFCS) for paddy field irrigation by employing information and communication technologies. The development of SFCS considered the requirement on rice growth, pest development, and fieldwork management. The proposed SFCS is equipped with a solar power supply system and consisted of sensors including illumination, air temperature, air humidity, water level, soil moisture content, soil electronic conductivity, and soil temperature. Narrowband Internet of Things (NB-IoT) is used for data transmission due to the data size and transmitting frequency. A smartphone-based application (APP) has been developed for users to monitor field environment by tabular, dashboard panel, and whisker chart box, provides multiple data display ways for different purposes. Moreover, a proposal for a water-saving irrigation technique named system of probiotics rice intensification (SPRI) has been integrated into the APP. With the developed APP, farmers will receive fieldwork reminders by calendar day that water-saving irrigation may be possibly implemented. The SFCS is not only shown ability on the field monitoring but also links the gap between the fieldwork application and modern technology.